Optimized pattern design of light-guide plate (LGP) - Kim, Young Chul; Oh, Tae-Sik; Lee, Yong Min (Oficyna Wydawnicza Politechniki Wrocławskiej, 2011)
We have investigated the light intensity distributions of a 7-inch LGP to increase output illuminance uniformity by reducing the bright and dark areas caused by a plurality of LED. We analyzed the effects of the LED–LED gap and LED–LGP space to the light intensity distribution in the LGP inside. We have found that the density function of LGP pattern has a simple exponential terms. We analyzed the output light intensity of the LGP through the comparison of the simulation results between adopting the hemisphere pattern density function and adopting the equidistance pattern density function. And also, to reduce the bright spot and dark areas, we have introduced a convex elliptical LED reflector. As a result, the output illuminance uniformity was improved effectively by the adoption of the pattern density function and the new LED reflector.
Optica Applicata, Vol. 41, 2011, Nr 4, s. 863-872
Keywords: optyka; TFT-LCD; backlight unit (BLU); light-guide plate (LGP); pattern density function; hot spot